Idee teologiczno-polityczne francuskiego duchowieństwa ultramontańskiego w czasie pontyfikatu Piusa IX (1846-1878) - WIELOMSKI, Adam (Historia i Świat, 2015)
This article presents the views of the French clergy on the theological and on the political during the counter-revolutionary and traditionalist pontificate of Pius IX (1846-1878). Its aim is show the many parallels and similarities between theological thought and political thought. In the era of subsequent political revolutions and the secularization French clergy look for the defender of Church. After the collapse of the catholic monarchy, the only possible defender is the Papacy. Ultramontanism program is the concept of the recognition of the Pope for the last point of defense before the Satan's revolution. Therefore Ultramontanism is a counter-revolutionary movement. Politics and religion come together in the great synthesis of the Catholic counter-revolution. The head of this movement the ultramontanes see in the Bishop of Rome.